Online Reading in the Classroom (Revista Peruana de Investigación Educativa, 2014)
In the context of the digital culture, ICT have impacted on every sphere of life. Education is another example, as it has suffered massive ICT introduction due to 1x1 (one laptop per child) initiatives across the globe. But there are few studies on how ICT are changing literacy practices in the classroom. In this paper, we explore and analyze the effects of ICT in the classroom: how teachers and students read with their laptops as well as how they perceive digital reading is shaping new ways of learning and creating knowledge. With a corpus of 81 ethnographic semistructured interviews, we will describe and analyze current reading practices as regards classroom textbooks, the reading of literary works, tests and additional assessment activities. This allows us to balance whether paper is still the dominant format or the digital component is gaining ground in these practices. Finally, we try to examine to what extent digital means pedagogical and methodological innovation.
Keywords: 1x1; digital reading; digital textbooks; pedagogical innovation